A Mechanistic Model of Drug‐Induced Liver Injury Aids the Interpretation of Elevated Liver Transaminase Levels in a Phase I Clinical Trial. (5th February 2014) - Howell, BA; Siler, SQ; Shoda, LKM; Yang, Y; Woodhead, JL; Watkins, PB
Abstract : Entolimod (CBLB502) is a Toll‐like receptor 5 agonist in development as a single‐dose countermeasure against total body irradiation. Efficacy can be assessed from animal studies, but the "Animal Rule" does not apply to safety assessment. Marked elevations of serum aminotransferases (exceeding 1, 000 IU/l) were observed in some human subjects receiving Entolimod in a safety study, threatening its continued development. The percentage of total hepatocytes undergoing necrosis in these subjects was estimated using a mechanistic, multiscale, mathematical model (DILIsym). The simulations suggested that no subject in the safety study experienced more than a modest loss of hepatocytes (<5%), which was comparable to estimates from a study of healthy volunteers receiving treatment with heparins. The predicted hepatocyte loss with Entolimod was lower than that required to cause liver dysfunction or that is routinely excised from volunteers donating for autologous liver transplantation and did not likely represent a serious health risk. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e98; doi:10.1038/psp.2013.74 ; published online 5 February 2014